2012
DOI: 10.1155/2012/952508
|View full text |Cite
|
Sign up to set email alerts
|

Folate Intake,MTHFRPolymorphisms, and the Risk of Colorectal Cancer: A Systematic Review and Meta-Analysis

Abstract: Background. The objective was to determine whether relationships exist between the methylene-tetrahydrofolate reductase (MTHFR) polymorphisms and risk of colorectal cancer (CRC) and examine whether the risk is modified by level of folate intake. Methods. MEDLINE, Embase, and SCOPUS were searched to May 2012 using the terms “folic acid,” “folate,” “colorectal cancer,” “methylenetetrahydrofolate reductase,” “MTHFR.” Observational studies were included which (1) assessed the risk of CRC for each polymorphism and/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
42
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(45 citation statements)
references
References 76 publications
3
42
0
Order By: Relevance
“…Previous meta-analyses have suggested inverse associations between higher folate intake and a reduced risk of cancer of the lung, pancreas, colon and other parts of the gastrointestinal tract (Dai et al, 2013;Kennedy et al, 2011;Larsson et al, 2006;Lin et al, 2013). In addition, genetic polymorphisms in folate metabolism have been associated with these malignancies (Kennedy et al, 2012;Larsson et al, 2006;Liu et al, 2012). However, some studies report that very high folate intakes, attributable to supplement use, may increase cancer risk.…”
Section: Discussionmentioning
confidence: 99%
“…Previous meta-analyses have suggested inverse associations between higher folate intake and a reduced risk of cancer of the lung, pancreas, colon and other parts of the gastrointestinal tract (Dai et al, 2013;Kennedy et al, 2011;Larsson et al, 2006;Lin et al, 2013). In addition, genetic polymorphisms in folate metabolism have been associated with these malignancies (Kennedy et al, 2012;Larsson et al, 2006;Liu et al, 2012). However, some studies report that very high folate intakes, attributable to supplement use, may increase cancer risk.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, folate deficiency has been shown to suppress DNA synthesis in neoplastic cells (102, 104). Epidemiological data on folate, however, have suggested that a high level of folate is associated with a reduction in risk of colorectal cancer (73, 9799, 179). Some clinical studies have also demonstrated efficacy (93, 154, 221), although other clinical studies have shown no or even detrimental effects of folate supplementation on colorectal cancer (37, 58, 124, 214).…”
Section: Introductionmentioning
confidence: 99%
“…A large, recent meta-analysis (24,816 cases) reported a reduced colorectal cancer risk when comparing highest (median, > 441 μg/day) with lowest (median, 212 μg/day) folate intake (RR 0.88; 95% CI 0.81-0.95)[17]. Using genetic studies, a meta-analysis of 67 studies reported strong evidence of association between the MTHFR 677TT genotype (which results in lower serum folate) and lower colorectal cancer risk under conditions of high folate intake[53].…”
Section: Discussionmentioning
confidence: 99%